Rehabilitation after Amputation: Psychotherapeutic Intervention Module in Indian Scenario - Kalpana Srivastava; Suprakash Chaudhury (The Scientific World Journal)
Psychological aspects of adjustment to amputation are varied and not addressed in the present treatment regime. There is no research evidence available of psychological intervention and outcome in Indian scenario. One hundred and seventy-three consecutive patients with limb amputations were randomly assigned to psychotherapeutic intervention module (PIM, study group) (n=90) and treatment as usual group (TAU, control group) (n=83). Patients with psychotic disorder were excluded from the study. Carroll Rating Scale for Depression (CRSD), State-Trait Anxiety Inventory (STAI), Amputees Body Image Scale (ABIS), and Impact of Event Scale (IES) along with specially designed information schedule were administered individually. Structured psychotherapeutic module was developed for the intervention. Patients in PIM group were given six therapy sessions, addressing the specific areas of concern. All patients were evaluated on the same tools after two months of therapy. Analysis showed that after treatment a significant reduction in scores was noted on CRSD, STAI, ABIS, and IES in the PIM group. On the TAU group a significant reduction was seen only in the ABIS. The psychological intervention module proposed by authors was efficacious in alleviating the psychological distress, depression, and anxiety and thus was vastly superior to the conventional method of management of amputees.